Transformasi Digital, Pengalaman Wisatawan, dan Loyalitas di Fulan Fehan - Herman Silver Crespo Koy; Apryanus Fallo; Engelbertus G.Ch. Watu (AKSIOMA : Jurnal Manajemen, 2026)
This study examines the effects of digital transformation and tourist experience on tourist loyalty at Fulan Fehan, with tourist satisfaction as an intervening variable. Using a quantitative survey design, data were collected from 96 visitors aged 17 years and above who had visited Fulan Fehan and were selected through purposive sampling. The data were analyzed with variance-based structural equation modeling using SmartPLS. The findings show that tourist experience has a positive and significant effect on satisfaction and loyalty. At the same time, satisfaction also has a positive and significant effect on loyalty and mediates the effect of tourist experience on loyalty. By contrast, digital transformation does not significantly affect satisfaction or loyalty. These results indicate that tourist loyalty at Fulan Fehan is shaped primarily by the quality of the on-site experience rather than by digital support alone.